KONFLIK TERSEMBUNYI MASYARAKAT BATAK TOBA ISLAM DENGAN BATAK TOBA KRISTEN DI PERUMNAS MANDALA KOTA MEDAN - Tanjung, Elvina; Syahminan, Mhd.; Muary, Rholand (CV. Kalimasada Group, 2024)
The purpose of this research is to find out the hidden conflicts that occur between the Islamic Toba Batak community and Christian Toba Batak in Perumnas Mandala Medan City and to find out the factors that cause hidden conflicts between the Islamic Toba Batak community and Christian Toba Batak in Perumnas Mandala Medan City. This research uses qualitative methods with data collection techniques such as observation, interviews, and documentation. This study found that the Islamic Batak Toba community and Christian Batak Toba have hidden conflicts, latent conflicts that occur between the Islamic Batak Toba community and Christian Batak Toba in Perumnas Mandala Medan City in the form of an assumption that the lack of tolerance from the Islamic Batak Toba causes disruption of the livelihood or economy of the Christian Batak Toba, the next latent conflict is that the Islamic Batak Toba community is uncomfortable with the presence of pigs belonging to the Christian Batak Toba because the aroma is so pungent and disrupts their activities, the next latent conflict is that the Islamic Batak Toba community is disturbed by the presence of tuak stalls in Perumnas Mandala Medan which disturbs the security and comfort of the local community. Factors that cause latent conflict between the Muslim Batak Toba and Christian Batak Toba communities are factors of individual differences, cultural differences between the Muslim Batak Toba and Christian Batak Toba communities and differences in interests. The steps used by the Toba Batak community in Perumnas Mandala Medan City, especially in Neighborhood IX Tegal Sari Mandala II in resolving latent conflicts are using democratic steps by providing opportunities for parties who have inner conflicts (pseudo conflict) to express their opinions, then using coercion by using their power or authority, then the last is using smoothing methods such as compromise or deliberation to get the best solution.